(untitled) (Research, Society and Development, 2024)
Objectives: to evaluate the primary outcome, pressure injury (PI) through intervention with multilayer silicone foam on bony prominences in patients at high risk for PU, and the secondary outcome, adverse events and related side effects. Methodology: single case study, carried out in the intensive care unit (ICU) of a federal university hospital in Rio de Janeiro, between May 2023 and March 2024, after approval by the Research Ethics Committee. Patients over 18 years of age with intact skin were included in the study. Development stages: risk assessment for PI (Cubbin & Jackson scale), anamnesis, physical examination and explanation regarding the research to the family member to sign the free and informed consent form. The intervention took place for 7 days, with foam on the right and left heel, maintained as a control, without foam. Results: primary outcome - absent LP and secondary - absence of adverse events and side effects. Conclusion: the foam did not cause any negative outcomes to the integrity of the skin, being safe for use. Regarding the limitation of the study, only one case and with intervention in only one anatomical topography - calcaneus, making it not possible to generalize its recommendation. Finally, multilayer silicone foam should be considered as an auxiliary resource in conjunction with internationally recommended PI prevention measures (NPUAP/EPUAP/PPPIA, 2019). It is worth remembering that PI is an adverse event and that the assessment of risk factors and their control must be a goal of patient safety and the promotion of quality in healthcare.